Voluntary isometric contractions at maximal shortening as a new warm-up exercise - Hernández-Trujillo, Julio-Artemi; González-Rivera, María-Dolores; González-Hernández, Jorge Miguel (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Research on isometric training states that strength levels depend on the length of the muscle at the moment of con-traction. So far, its effects have been studied at different joint ranges, except at maximal muscle shortening. Ballistic stretching (BS) is also used in sports to achieve maximal ranges of joint mobility. The present study examined the acute effects of voluntary isometric contractions at maximal shortening (VICAMS) on shoulder range of motion, strength, and throwing and compared them with BS.Methods. Sixty physically active participants volunteered to participate and were randomly assigned to one of three in-terventions: BS, VICAMS, and a control group (CG). Active range of motion (AROM), maximal voluntary isometric strength (MVIF), and one-handed [unilateral seated shot-put throw (USSPT)] and two-handed [seated shot-put throw (SSPT)] throws were measured before and after the intervention.Results. After setting the significance level at p < 0.05, main effects were found for time and time*group interactions for all variables (p < 0.001). Between-group differences were observed in the VICAMS group after the intervention, with signifi-cantly higher AROM and MVIF values compared to the other groups. Intra-group differences were observed in the VICAMS and BS groups, as the values of all three variables increased from baseline.Conclusions. Applying VICAMS on the shoulder induced superior acute improvements than BS in flexibility, strength, and throwing ability, indicating that a new warm-up could be developed. Coaches should consider these findings as they offer a practical and effective solution for immediate performance improvement.
Keywords: isometric training; ballistic stretching; shortened muscle position; maximal strength; AROM